Histopathological Study of Ovarian Lump and Serum Tumor Marker Ca 125 estimation as a Screening Tool (Journal of Nobel Medical College, 2018)
Background: Ovarian tumor is the fourth commonest cancer in female in Nepal. About 80% is benign and 20% of these tumors are malignant. Due to its complex nature, vagueness and non-specificity of the symptoms it produces, the ovarian neoplasm can mislead both the doctor and patients. Hence this study was undertaken with aims & objectives to study the morphology of ovarian specimens as well as estimate serum CA125 as screening tool. Material and Methods: A study of over one year comprised of 75 specimens of ovary diagnosed in the Department of Pathology, Nobel medical college and teaching hospital, Biratnagar. After thorough gross examination and preparation of H&E stained slides the lesion of ovary were classified as per WHO classification. Also, preoperative blood samples were obtained from patients for estimation of serum CA125 level. Blood samples was also drawn from 20 healthy females in reproductive age group who acted as controls. Results: Of the 75 cases of ovarian mass, based on histology 75% were benign, and 25% were malignant. Surface epithelial tumors were the commonest (68%) of all ovarian tumor, followed by germ cell tumors (13%), sex cord–stromal tumors (6%). Serous Cystadenoma (29%) was the commonest benign tumor and serous cystadenocarcinoma (9%) commonest malignant neoplasm.  CA125 levels was raised in epithelial ovarian cancers. Maximum rise was seen in serous cystadenocarcinoma. Exceptionally a small percentage of epithelial cancer showed normal level (false negative). Also, few benign tumors, non-epithelial tumors and even non-neoplastic lesions showed false positive rise in CA125 (false positive). Conclusion: Accurate histopathological evaluation of ovarian specimen is necessary both in terms of therapeutic intervention as well as prognosis.  CA125 is an important screening tool for detection of epithelial ovarian cancers. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 30-36